Pendidikan Karakter Berbasis Akhlaq - Saifulhaq Inaku; Muhammad Nur Iman (Irfani (e-Journal), 2020)
Character education is the mandate of the Pancasila and the 1945 Constitution, so that the government makes character development as one of the national development priority programs. There have been many concepts of character education offered in the world of education, but what concerns the author is Character Based Moral Education. This research is a documentary research study whose study focuses on the analysis or interpretation of written materials based on the context. The material is in the form of published notes, textbooks, newspapers, manuscripts, articles, and the like. The results showed that character-based character education leads to the creation of the character of students who are experts in worship, have moral values, namely morals to God, morals to both parents, morals to teachers, morals to others, to be good citizens, to do good citizenship good deeds for all humanity. This journal certainly has shortcomings, therefore constructive criticism and suggestions are expected for its perfection.